Inequality in the Indian Water Sector: Challenges and Policy Options. Issue 2 (August 2018) - Kumar, M. Dinesh; Saleth, R. Maria
Utilizing illustrative examples based on empirical data, this article attempts to provide an indicative assessment of the growing magnitude of inequality in access to water in India. This assessment was made within an analytical framework that highlights variations across water-using sectors such as rural agriculture and urban, as well as across different sources of water such as groundwater, surface water and others. The dimensions of inequality analysed include: inequality in access to common pool groundwater resources (both inter-generational and intra-generational inequality); inequality caused by monopolistic groundwater markets; inequality in access to common property water from river catchments; inequality in access to subsidized water from public irrigation schemes; and inequality in access to water from municipal water supply systems. The article also discusses the role of major factors which contribute to the inequality in the access to water in different contexts, such as lack of well-defined water use rights, inequality in the ownership of land and other rural assets, spatial and topographical issues such as tail-end and downstream aspects, ineffective water and energy pricing policies, inadequate or poorly designed infrastructure and suboptimal water sector investment. The article concludes by providing feasible policy options and possible implementation principles to reduce inequality in access to water across sectors, sources and regions.